Spirit of the Paekche [videorecording] - Chung, Jaeshin; Heo, Baekkyu; Kim, Kidong; Song, Hwa (Timeless journey)
A journey through the south Chungchong province. Explores the ginseng market, traditional houses, ceramic art villages, pottery and folk festivals.